The 2021 WHO classification for gliomas and implications on imaging diagnosis: Part 3, summary of imaging findings on glioneuronal and neuronal tumors - Park, Yae Won; Vollmuth, Philipp; Foltyn-Dumitru, Martha; Sahm, Felix; Choi, Kyu Sung; Park, Ji Eun; Ahn, Sung Soo; Chang, Jong Hee; Kim, Se Hoon (Journal of magnetic resonance imaging, 2023)
The fifth edition of the World Health Organization classification of central nervous system tumors published in 2021 reflects the current transitional state between traditional classification system based on histopathology and the state-of-the-art molecular diagnostics. This Part 3 Review focuses on the molecular diagnostics and imaging findings of glioneuronal and neuronal tumors. Histological and molecular features in glioneuronal and neuronal tumors often overlap with pediatric-type diffuse low-grade gliomas and circumscribed astrocytic gliomas (discussed in the Part 2 Review). Due to this overlap, in several tumor types of glioneuronal and neuronal tumors the diagnosis may be inconclusive with histopathology and genetic alterations, and imaging features may be helpful to distinguish difficult cases. Thus, it is crucial for radiologists to understand the underlying molecular diagnostics as well as imaging findings for application on clinical practice. Evidence Level 3 Technical Efficacy Stage 3
Online veröffenticht: 16. September 2023
Gesehen am 14.11.2023